Discussing Gender among Right-Wing Men: Censorship, Dilemmas and Dissents Between Spanish Conservatives and Radicals - Alexandre Pichel-Vázquez; Marta Cabezas Fernández; Begonya Enguix Grau (Asparkía)
The reappearance of the Spanish far right (Vox) in institutional politics has destabilized the conservatives’ (PP) hegemony on the right and has ended an apparent democratic consensus around gender issues, particularly among right-wing men. Through a qualitative and emic approach, this article aims to explore the negotiations, dilemmas, and contradictions within right-wing gender politics as expressed by their male voters. We conducted a focus group with seven Spanish right-wing men and analyzed their unique conversation from a conception of discourse as an interactional-social practice. The discussion evolved through different stages of censorship, negotiation, and conflict. This article shows how gender is at the core of politics and creates both connections and conflicts on the right.